Pengaruh Perpindahan Panas Pipa Kalor Pada Posisi Horizontal - Ruben Siregar; Rahmat Iman Mainil; Azridjal Aziz (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Heat pipes are devices that can transfer heat from one point to another point very quickly at a constant temperature difference, with large heat transfer capacity. Heat pipe used in a wide variety of manufactured products, such as laptops, mobile phones, and others. Solid copper and heat pipes are make to have a diameter of 3/8 "and with a length of 40 cm with a filling ratio of 10%. Solid copper and heat pipe was tested in the horizontal position and temperature data obtained in the evaporator section, adiabatic and condenser. Heat transfer rate of heat pipe using wick is 8.82 W, without using wick is 8.36 W and with solid copper is 1.22 W. The thermal conductivity of the heat pipe without wick 5291.18 W / mK and then use wick 6294.69 W / mK, solid copper 75.42 W / mK. Comparison of thermal conductivity between a heat pipe using wick with a copper solid is 83.46 times higher.Keywords : heat pipe, filling ratio, wick